Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/ncb774
|View full text |Cite
|
Sign up to set email alerts
|

Myosin IXb is a single-headed minus-end-directed processive motor

Abstract: Myosin is an actin-based molecular motor that constitutes a diverse superfamily. In contrast to conventional myosin, which binds to actin for only a short time during cross-bridge cycling, recent studies have demonstrated that class V myosin moves along actin filaments for a long distance without dissociating. This would make it suitable for supporting cargo movement in cells. Because myosin V has a two-headed structure with an expanded neck domain, it has been postulated to 'walk' along the 36-nm helical repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 30 publications
2
75
1
Order By: Relevance
“…The mean actin translocating velocity was 0.11 Ϯ 0.05 m/s that was significantly slower than other myosin superfamily members (31, 35, 38 -42). Interestingly, high Ca 2ϩ concentration did not abolish the motility activity of human myosin III in contrast to other calmodulin binding myosins such as myosin V (31,35), myosin I (27, 43), and myosin IX (41).…”
Section: Figmentioning
confidence: 85%
See 1 more Smart Citation
“…The mean actin translocating velocity was 0.11 Ϯ 0.05 m/s that was significantly slower than other myosin superfamily members (31, 35, 38 -42). Interestingly, high Ca 2ϩ concentration did not abolish the motility activity of human myosin III in contrast to other calmodulin binding myosins such as myosin V (31,35), myosin I (27, 43), and myosin IX (41).…”
Section: Figmentioning
confidence: 85%
“…It was originally hypothesized that the unique large insertion of myosin VI between the motor domain and the neck domain was responsible for the reverse directionality of motility, thus making the class VI myosin the only minus-directed myosin. However, recent studies have revealed that this is not the case and that there are additional members in the myosin superfamily that move in the minus direction (29,41). To determine the direction of movement of human myosin III, we utilized F-actin filaments in the in vitro motility assay that were labeled throughout with fluorescein and labeled with a rhodamine cap at the filament's pointed end (see "Experimental Procedures").…”
Section: Figmentioning
confidence: 99%
“…In class VI myosin, calmodulin was found to be associated with a unique insert between the converter and the IQ-motif that repositions the lever arm and reverses directional movement of myosin VI toward the minus-end of actin filaments (37,38). A human recombinant Myo9b construct that was truncated in the tail region was reported to move toward the minus-end of actin filaments (6). By contrast, native full-length Myo9b was reported to be a plus-, and not a minus-end directed motor, suggesting that the tail domain of Myo9b regulates motor directionality (24).…”
Section: Discussionmentioning
confidence: 99%
“…Native Myo9b immunoadsorbed from human leukocyte extracts moved toward the plus-end of the actin filament (24). However, a truncated recombinant Myo9b was reported to move toward the minusend of the actin filament (6). The reason(s) for this difference in Myo9b directionality is not known.…”
mentioning
confidence: 99%
“…The minus-end of an actin filament or a microtubule can be fluorescently labeled to distinguish it from the plus-end. Using this technique, it was discovered that, different from conventional kinesin, the kinesin-related protein motors ncd [26] and Kar3 [27] are minus-end-directed microtubulebased motors and, different from conventional myosin, myosin VI [28,29] and myosin IX [30] are minus-end directed actin-based motors.…”
Section: Backwards Directed Movementmentioning
confidence: 99%